Improving Students Honesty Behavior Through English Subject - Depi Prihamdani; Andes Safarandes Asmara; Haerudin Haerudin; Harmawati Harmawati; Anggy Giri Prawiyogi (Universitas Pahlawan Tuanku Tambusai, 2021)
The aim of this study is to analyze the effectiveness of the role of English subject to implant and to improve students’ university behavior to be honest, do not cheat on the test, and do not corrupt on their daily life. Subject of this study is the first semester student of PGSD the academic year of 2019/2020 University of Buana Perjuangan Karawang. In order to reach the goal of this study the writer uses qualitative research method with descriptive qualitative approach. While, technique of data collecting is done by observing, field studying, interviewing and documenting. The result of this study is expected to be able to have a contribution and is useful for all related parties, especially university or college in order to build students’ behavior to be honest, do not cheat on the test and do not corrupt in their life